The Analysis of Character and Characterization of Alif in the Novel Ranah 3 Warna by Ahmad Fuadi and its Implication to Literatur Learning in Senior High School - Putriana, Erika; Nurhadi, Nurhadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to (1) describe the character and characterization of Alif in Ahmad Fuadi's novel *Ranah 3 Warna* and (2) explore the implications of this analysis for high school literature education. Employing a descriptive qualitative research method, data was collected through library techniques utilizing written sources, focusing on the novel's content (phrases, words, sentences, prologue, and dialogue). Data analysis followed a flow model, and the validity and reliability were tested through semantic validity and intrarater reliability. The findings reveal that Alif exhibits three character dimensions: physiological, sociological, and psychological. Various techniques used in his characterization include conversation, behavior, thoughts and feelings, flow of consciousness, character reactions, and physical depiction. Alif's character and characterization have implications for high school literary learning, specifically addressing KD 3.9 and KD 4.9 related to analyzing and designing novels